Uslub Al-Hikmah, Al-Mau’izah Al-Hasanah dan Mujadalah Bi Al-Husna Mengikut Pandangan Ulamak - Hj Syed Hussin, Syed Abdurahman (Jurnal Usuluddin, 1996)
This article tries to indentify al-Hikmah, Maui’zah al-Hasanah and Mujadalah bi allati hiya Ahsan as methods of da’wah according to the ulama opinions.